The Role of Mentimeter in Increasing Classroom Interaction and Participation - Sianipar, Rimma; Sinaga, Andromeda Valentino; Stefanie Inggried Gorap; Sihombing, Liston (English Lecturers and Teachers Association (ELTA), 2025)
This study investigates the role of Mentimeter in activating students to be more engaged in the Universitas Negeri Makassar Educational Technology Study Program. Utilizing both quantitative and qualitative methods, data were collected from a total of 20 participants (n = 20) through questionnaires, observations, and interviews. The results are that Mentimeter activates students to be more active (50% strongly agree, 40% agree) and freer to respond (55% strongly agree, 35% agree). Interactive features such as polling, word cloud, and anonymous Q&A were rated as engaging by 60% of students strongly agreeing and 30% agreeing. The application in understanding the material was strongly agreed by 45% and agreed upon by 38%, while 12% were neutral and 5% disagreed. Additionally, 58% strongly agreed and 32% agreed that Mentimeter should be adopted by other courses. This study confirms that Mentimeter is able to create a heightened interactive and engaging learning environment despite constraints such as overreliance on internet connectivity as well as educator preparedness.